The long and short of financing government spending - Jochen Mankart; Romanos Priftis; Rigas Oikonomou (National Bank of Belgium, 2022)
This paper shows that debt-financed fiscal multipliers vary depending on the maturity of debt issued to finance spending. Utilizing state-dependent SVAR models and local projections for post-war US data, we show that a fiscal expansion financed with short term debt increases output more than one financed with long term debt. The reason for this result is that only the former may lead to a significant increase in private consumption. We then construct an incomplete markets model in which households invest in long and short assets. Short assets have a lower return (in equilibrium) since they provide liquidity services, households can use them to cover sudden spending shocks. An increase in the supply of these assets through a short term debt financed government spending shock makes it easier for constrained households to meet their spending needs and therefore crowds in private consumption. We first prove this analytically in a simplified model and then show it in a calibrated standard New Keynesian model. We finally study the optimal policy under a Ramsey planner. The optimizing government faces a trade-off between the hedging value of long term debt, as its price decreases in response to adverse shocks, and the larger multiplier when it issues short term debt. We find that the latter effect dominates and that the optimal policy for the government is to finance spending predominantly with short term debt.
Keywords: D52; E31; E43; E62; 330; Spending multiplier; Fiscal Policy; Debt Maturity; Incomplete Markets; SVAR; Local Projections